2018
DOI: 10.3390/toxins10090368
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Intrastriatal Botulinum Neurotoxin-A Injection in Hemiparkinsonian Rats Increased the Beneficial Effect on Rotational Behavior

Abstract: Injection of botulinum neurotoxin-A (BoNT-A) into the striatum of hemiparkinsonian (hemi-PD) rats reduced apomorphine-induced rotation behavior significantly, for at least 3 months. Thereafter, rotation behavior increased again. We injected hemi-PD rats with 1 ng BoNT-A twice, the second injection following 6 months after the first one and tested the rats for apomorphine-induced rotations and spontaneous motor behaviors, i.e., corridor task and stepping test. To test the hypothesis that BoNT-A reduced striatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 101 publications
1
19
0
Order By: Relevance
“…One month after injection of 6-OHDA into the right MFB, the respective values were: left paw forehand: 3.958 ± 0.136, left paw backhand: 6.813 ± 0.136, right paw forehand: 10.993 ± 0.160, right paw backhand: 12.153 ± 0.175 ( Figure 3 B and Figure 5 B). Neither the first nor the second BoNT-A injection into the CPu significantly changed the number of AS made by either forepaw in either direction [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One month after injection of 6-OHDA into the right MFB, the respective values were: left paw forehand: 3.958 ± 0.136, left paw backhand: 6.813 ± 0.136, right paw forehand: 10.993 ± 0.160, right paw backhand: 12.153 ± 0.175 ( Figure 3 B and Figure 5 B). Neither the first nor the second BoNT-A injection into the CPu significantly changed the number of AS made by either forepaw in either direction [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the ITs of movements of left and right forepaws both in forehand and backhand directions and apomorphine-induced rotations in individual rats 1 month after induction of hemi-PD revealed that these parameters are not significantly correlated ( Figure 5 A). Rotational behavior covered a wide range of values (−0.775 to +12.022 rpm; [ 58 ]). However, ITs were found rather constant (left paw: 2.600–4.827 s, right paw 0.424–0.813 s).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations